2001
DOI: 10.1183/09031936.01.00056201
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis severity and socioeconomic status

Abstract: Several chronic diseases are more severe in persons who are Black, of low socioeconomic status (SES), and underinsured. The authors ask if this is true for sarcoidosis. Associations among sarcoidosis disease severity, SES, insurance coverage, and functional limitations were analysed.Back and White sarcoidosis patients (n=110) of a municipal and university hospital sarcoidosis registry were interviewed by telephone. Data on disease severity were abstracted from patient charts.Most patients reported good or exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 15 publications
1
26
0
3
Order By: Relevance
“…Furthermore, patients with private health insurance were more likely to report no limitations, while, at the same time, they more often indicated that they were limited in particular kinds of activity. With regard to social limitations, patients with private insurance were again more likely to report no limitations [60]. Thus, in general, patients with a high socioeconomic status reported a better health status.…”
Section: Health Status In Sarcoidosismentioning
confidence: 81%
“…Furthermore, patients with private health insurance were more likely to report no limitations, while, at the same time, they more often indicated that they were limited in particular kinds of activity. With regard to social limitations, patients with private insurance were again more likely to report no limitations [60]. Thus, in general, patients with a high socioeconomic status reported a better health status.…”
Section: Health Status In Sarcoidosismentioning
confidence: 81%
“…It was observed that a lower SES and no or public insurance were associated with worse health status and more severe dyspnea. More advanced radiographic stage was associated with lower income, and forced vital capacity impairment with less education [55]. Patients who had incomes less than $20,000 a year were 3.5 times more likely to have Stage 3-4 disease than patients with an income greater than $50,000 a year.…”
Section: Sarcoidosismentioning
confidence: 84%
“…Studies analyzing sarcoidosis in relationship to SES have been outlines in Table 5. In the first study to look at disease severity in correlation with SES was Rabin et al [55]. It was observed that a lower SES and no or public insurance were associated with worse health status and more severe dyspnea.…”
Section: Sarcoidosismentioning
confidence: 99%
See 1 more Smart Citation
“…Blacks are more likely to be of low SES and to be insured less well. Cross-sectional studies of ambulatory sarcoidosis patients showed education, income and/or public health insurance to be related to disease severity [4]. Among Black patients, municipal hospital ambulatory sarcoidosis patients had more severe illness than university hospital sarcoidosis patients [5].…”
mentioning
confidence: 99%